A mídia globalizangte e a abolição do mito: o ocaso de uma cultura? - Martins, Maria Angélica Seabra Rodrigues [UNESP] (My University, 2010)
The globalization in the last century made possible to the human bean to know everything about all cultures in the world. Although the knowledge conduct many people to leave the tradition of their society in order to adopt the new values that could cause the abandon of the tradition.